Corporate Ethical and Legal Responsibility:Effects of CSR on Consumer Trust and Brand Loyalty - Manimalar, R.; Sudha, S. (Prabandhan: Indian Journal of Management, 2016)
Although, community issues are important, the researchers have identified general CSR such as charity, cultural, and social contributions, protecting the natural environment. Consumers demand other types of activities to label a socially responsible company. This paper proposed and tested a conceptual framework model of CSR that identified an association between the two components of CSR and their effects on consumer trust and brand loyalty. The ethical and legal components of CSR initiatives were taken as an independent variable, and consumer trust and brand loyalty were taken as the dependent variables. A structural equation model was tested using a sample of 261 consumers. Mall intercept sampling was used to determine the samples. CFA was used to validate the constructs in the questionnaire. Reliability and validity were tested using convergent validity and discriminant validity test. The SEM analysis revealed that the brand’s fulfillment of both ethical CSR initiatives and legal CSR initiatives had a direct positive impact on brand loyalty and consumer trust. The ethical responsibility had a high correlation with brand loyalty and on consumer trust than on legal responsibility. The results of this research paper suggest that companies should take consumer trust into account when forming their CSR and communication strategies. This will create a positive image in the minds of the consumers and will bring a positive word of mouth. The paper provides possible guidance for companies to be more efficiently positioned and communicate their CSR actions to create differential competitive advantages.